RE: Miniaturized percutaneous nephrolithotomy versus retrograde intrarenal surgery in the treatment of renal stones with a diameter <15 mm: A 3‑year open‑label prospective study - Kamarulzaman, Mohd Nazli (Wolters Kluwer - Medknow, 2020)
I read with great interest the article “Miniaturized percutaneous nephrolithotomy versus retrograde intrarenal surgery (RIRS) in the treatment of renal stones with a diameter <15 mm: A 3‑year open‑label prospective study” by Mhaske et al. [1] This article highlights important findings regarding the safety and efficacy of both mini‑percutaneous nephrolithotomy (mini‑perc) and RIRS. In most of the previous similar comparative study, renal stone size <2cm was used as a cutoff point. It is an eye‑opening to reduce the size to <1.5cm and to compare the efficacy of both procedures. However, the other study by Suresh et al. taken a more specific size as cutoff point which was between 1 cm and 1.5 cm.[2] This will better prospective as moss of stone <1 cm can be treated with extracorporeal shock wave lithotripsy. As stated by the author, the objective of this study was to compare between mini‑perc and RIRS regarding stone‑free rate, retreatment rate, complications, hospital stay, operative time, and reduction in hemoglobin level. The result shows that there was statistically significant difference in term of operative time but not different in‑hospital stay.